2015
DOI: 10.3325/cmj.2015.56.239
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of blood, buccal swabs, and hair follicles for DNA profiling technique using STR markers

Abstract: AimTo study the short tandem repeat (STR) pattern of DNA from the blood, buccal swabs, and hair follicles of the recipients of allogenic hematopoietic stem cell transplantation to examine whether these tissues contain donor derived cells.MethodsThe study enrolled 25 patients who sustained engraftment. Peripheral blood, buccal swabs, and hair follicles were collected on days 21-30, 90, and 180 after transplantation and the chimeric status of the recipients was evaluated.ResultsDonor derived cells existed in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…For hair follicle samples, no donor chimerism has been observed; thus, they can be used as a reliable biological source for personal identification by DNA profiling. Great care must be taken to avoid possible contamination while collecting the samples (17). It has been shown that peripheral blood DNA profiles of recipients show donor chimerism after successful allo-PBSCT.…”
Section: Discussionmentioning
confidence: 99%
“…For hair follicle samples, no donor chimerism has been observed; thus, they can be used as a reliable biological source for personal identification by DNA profiling. Great care must be taken to avoid possible contamination while collecting the samples (17). It has been shown that peripheral blood DNA profiles of recipients show donor chimerism after successful allo-PBSCT.…”
Section: Discussionmentioning
confidence: 99%
“…E very nucleated cell contains deoxyribonucleic acid (DNA) and analysis of this genome gives insight to the individuals' unique genetic identity and potential risk status for falling ill with genetic diseases (Sugata et al, 2002;Chaudhary et al, 2015;Fiorani and Cinotti, 2020). In the clinical sector, predictive screening, diagnostic testing for certain genotypes, possible somatic or germline mutations, biomarkers, and epigenetic anomalies can provide insight about a patient's predisposition for a certain disease or individual tolerance of drugs and treatments in the field of personalized medicine (Marteau and Croyle, 1998;Rahner and Steinke, 2008;Jostins and Barrett, 2011;Roberts et al 2012;Whirl-Carrillo et al, 2012;Cascella et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Chimerism is defined in transplantation medicine as the coexistence ofcells of, both, donor and recipient origin (Ten Hove et al, 2007). In previous studies, blood, hair samples and buccal swabs are studied as sources of DNA profiling after hematopoietic stem cell transplantation (Hong et al, 2007;Zhou et al, 2011;Li et al, 2014;Chaudhary et al, 2015;Santurtún et al, 2017) The partial chimerism is detectable predominantly in the P hematopoietic system developed by transfusion or transplantation of allogenic hematopoietic stem cells (Milde et al, 1999). This experimental work aims at studying the possibility of postmortem detection in DNA chimerism in liver tissue, after allogeneic hematopoietic stem cell transplantation.…”
Section: Introductionmentioning
confidence: 99%